Student-university communication media using web 2.0 - Qasem Saeed, Faisal Abdulkarem (2010)
Web 2.0 has become very widely to develop many web-based systems. Web 2.0 tools have changed the nature of web-based applications especially those are used for communication purposes. The Forums, Wikis, Blogs, Social Networking, Video Sharing and other Web 2.0 tools are used to communicate web users with each other in effective way for many purposes. In Universiti Technologi Malaysia (UTM), the communication process between postgraduate students and School of Graduate Studies (SPS) is done by Face-to-Face, phone, fax, Email and post. There are many communication problems encountered by the postgraduate students before and after they registered as students. This project was conducted to propose a Student- University Communication Media model using the Web 2.0 and use it to develop a prototype of Web 2.0-based Student-University Communication Media Portal. The Object Oriented Approach was used to develop the prototype of Web 2.0-based Student-University Communication Media Portal. Eventually, the prototype was implemented and tested. However, the organizational strategy of implementing the prototype by SPS was formulated. The User Acceptance Testing was conducted by thirty users with more than 95% of them satisfied with the developed portal and confirmed that it is easy to use, functional and useful.